Finding gene network topologies for given biological function with recurrent neural network - Jingxiang Shen (Nature Portfolio, 2021)
Networks are useful ways to describe interactions between molecules in a cell, but predicting the real topology of large networks can be challenging. Here, the authors use deep learning to predict the topology of networks that perform biologically-plausible functions.